(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Coronavirus disease 2019 (COVID-19) is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). It is possible for SARS-CoV-2 to produce multiorgan failure (MOF), which can be fatal. The purpose of this review is to assess the amounts of certain minerals (zinc, iron, and selenium) then vitamins (C, A, D, and E) in coronavirus-infected persons. Every study we looked at showed deficiencies in the aforementioned vitamins and minerals. We come to the conclusion that the immune depends heavily on micronutrients, and that the immune system is significantly impacted by their inadequacies. It has been proposed that increasing antioxidant intake can improve immunity, even though the majority of antioxidants are thought to be found in food. Despite the immune system’s continuous activity, the presence of pathogens increases the activation of specialized immunity. The expression of genes in immune cells is regulated by the metabolites of vitamins A, D, and other nutrients. The imaginable healing welfares of vitamins C, A, D, and E through immunomodulation in COVID-19 patients are assessed and investigated in this study. We discovered that zinc, iron, and selenium—essential micronutrient minerals—have antioxidant and antiviral qualities that strengthen the body’s defenses via a variety of mechanisms and immunomodulatory pathways.